Analisis Strategi Pemasaran pada Kerta Cafe dalam Upaya Memulihkan Ekonomi Pasca Pandemi Covid-19 - Muhammad Haris Fadhillah; Shofwan Azhar Solihin; Defitri Nugrahyani (Coopetition : Jurnal Ilmiah Manajemen, 2022)
The purpose of this research is to analyze marketing strategy for competitive advantage. The method used in this research is SWOT analysis to examine alternatives of strategies to be applied. The results of SWOT analysis in Kerta Cafe is aggressive strategy, the right alternative strategy is SO strategy that allows Kerta Cafe to use all of its strengths maximally to make the most of opportunities.